Physiological Changes in the Autonomic Nervous System Under Chronic Stress: A Systematic Review - Taha, Donia Hisham; Alwahab, Doaahassan Abd; Obiad, Rawaa Mohammed (Journal of Science in Medicine and Life, 2025)
Chronic stress profoundly disrupts autonomic nervous system (ANS) function. We systematically reviewed recent (2019–2024) literature to synthesize how sustained stress alters sympathetic and parasympathetic activity, related biomarkers, and health outcomes. We identified 20 peer-reviewed studies and 10 master’s theses on chronic stress and ANS physiology. Consistently, chronic stress induces sustained sympathetic hyperactivity (elevated catecholamines, heart rate, blood pressure) and parasympathetic suppression (reduced vagal tone, low HF power in heart rate variability (HRV) Biomarkers such as cortisol, ACTH, catecholamines, glucose, lipids, and inflammatory markers (CRP, IL-6/8) are frequently altered. Clinically, these ANS changes contribute to higher cardiovascular risk (hypertension, ischemia, arrhythmia) and immune dysregulation. We highlight methodological trends (HRV and neuroimaging metrics), gaps (lack of standardized stress definitions, causal studies), and implications for health.